Mapping of Employee Engagement Research: Bibliometric Analysis during 2016-2022 - Sutopo Sutopo; Agus Rahayu; Disman Disman; Lili Adi Wibowo (Budapest International Research and Critics University, 2022)
Scholars and practitioners point out that the current low level of employee engagement in the workplace is one of the most worrisome global economic problems. The potential consequence of this phenomenon is a decline in job performance. Therefore, it becomes essential to understand the concept of work engagement, its meaning for employees, and its implications for employers. This study examines the development of research on the topic of employee engagement. The study aims to determine: (1) the development of the number of international publications in the field of employee engagement in the Google Scholar database from 2016-2022; (2) core journals in international publications on the topic of employee engagement, (3) a map of the development of international publications in research fields with the topic of employee engagement, based on co-words. Collecting data by conducting searches through Publish or Perish (Pop) with the keyword’s employee, engagement, employee, with the category of the article title, abstract, and keywords in the period 2016-2022. Data in the form of the number of publications per year, publishers, and journals containing articles on employee engagement and subjects were analyzed using Microsoft Excel. Meanwhile, the trend of topic mapping was analyzed using VosViewer software. The study results show that the 2016-2022 growth development of Google Scholar indexed articles in 2020 reached 193 publications (19.3%). Most international publications are published in the International Journal of Management Review as many as 17 articles. The results showed that the research on employee engagement was still dominated by transformational leadership and organizational culture. For further research, the authors suggest the need for additional data sources so that more research results are more accurate and comprehensive.